(3GTcGdjI GdJfejI GdhWf GdYQHj (B/s - (3MGeO, SgjQs ((3YeGf(B: s (3OGQ GdTQhb ddfTQ(B, s, 2007)
(3GdeMJhjGJ (B: (3GdebOeI(B-(3GdaUd GdChd (B: (3GdJfejI hGdJNda (B: (3GdeaGgje hGdfXQjGJ hJWhQgG GdJGQjNj (B: (3XghQ hJWhQ eaghe GdJfejI (B: (3GdGJLGgGJ GdfXQjI aj GdJfejI (B: (3fXQjI GdJMOjK (B: (3NUGFU GdfXQjI (B: (3eHGOF fXQjI GdJMOjK (B: (3fbO fXQjI GdJMOjK (B: (3fXQjI GdJHYjI (B: (3NUGFU fXQjI aQGfc (B: (3GdGfJbGOGJ GdehLgI dfXQjI aQGfc (B: (3fXQjI GdJfejI GdHOjdI(B-(3GdaUd GdKGfj (B: (3GdJQcjH GdGLJeGYj hGdGbJUGOj ddhWf GdYQHj (B: (3CfeGW GdEfJGL hGdJTcjdGJ eG bHd GdQCSeGdjI (B: (3GdeQMdI GdGSJYeGQjI hGSJZdGd GdHdOGf GdYQHjI (B: (3GdJThgGJ GdCSGSjI GdJj CMOKgG GdGSJYeGQ aj GdHfjI GdGbJUGOjI GdGLJeGYjI aj GdHdOGf GdYQHjI (B: (3GdHdOGf GdYQHjI hNUGFU HfjJgG GdGbJUGOjI (B: (3GdGSJQGJjLjGJ GdOhdjI aj GdHdOGf GdfGejI (B((3GdhWf GdYQHj fehPLG(B)-(3GdaUd GdKGdK (B: (3CReI GdJfejI aj GdhWf GdYQHj (B: (3LghO GdJcGed GdGbJUGOj GdYQHj (B: (3GdhdGjGJ GdeJMOI hGdfXGe GdTQb ChSWj (B: (3GdfaW hGdJcGed GdGbJUGOj GdYQHj hOhQg aj GdJfejI (B: (3GdJHYjI GdGbJUGOjI aj GdhWf GdYQHj (B: (3CKQ GdYhGed GdGbJUGOjI hGdGLJeGYjI Ydi CReI GdJfejI(B-(3GdaUd GdQGHY (B: (3GdYhdeI hJOGYjGJgGYdi GdhWf GdYQHj (B: (3GdJWdYGJ hGdJMOjGJ CeGe GdGbJUGO GdYQHj (B: (3GdYhdeI (B: (3GdCgejI GdGbJUGOjI ddOhd GdYQHjI (B: (3GdJcGed GdGbJUGOj GdYQHj (B: (3GdJYGhf GdEbdjej GdYQHj (B: (3GdYed GdYQHj dehGMgI BKGQ GdSjGSI GdGbJUGOjI GdChQhHjI(B-(3GdaUd GdNGeS (B: (3GdfJGFL GdYGeI hGdMdhd(B.s
(3HjHdjhZQGajG(B: (3U(B. 185s
Keywords: (3GdJfejIs; (3GdJfejI GdGLJeGYjIs; (3GdJfejI GdGbJUGOjIs; (3GdJfejI(B- (3GdYGde GdYQHjs